Financial Market Imperfections and the Pricing Decision of Firms: Theory and Evidence - Almut Balleer; Nikolay Hristov; Michael Kleemann; Dominik Menno (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper investigates how financial market imperfections and nominal rigidities interact. Based on new firm-level evidence for Germany, we document that financially constrained firms adjust prices more often than their unconstrained counterparts. In particular, financially constrained firms do not only increase prices, but also decrease prices more often. We show that these empirical patterns are consistent with a partial equilibrium menu-cost model with financial frictions. Our results suggest that tighter financial constraints are associated with higher nominal rigidities, higher prices and lower output. Furthermore, financial recessions may induce very different dynamics than normal recessions if the relative size of unexpected financial shocks is large relative to aggregate price shocks.
Keywords: E31; E44; E32; 330